Acculturation and Accounting Standardization Strategies - Rahma Ben Salem; Salma Damak Ayadi; Rahim Kallal (Journal of Accounting and Management Information Systems (JAMIS), 2019)
Research question: The objective of this research is to develop a reliable and valid measurement scale for releasing new cultural attributes based on social psychology concepts and apply them afterwards in the accounting field. Motivation: Migration to International Accounting Standards Board (IASB) standards by a large and growing number of countries has marked the accounting field. However, this application varies from one country to another due to several environmental factors especially cultural ones. Idea: This paper puts the important issue of cultural differences in applying international financial reporting standards (IFRS) to the forefront and especially the strategies countries may apply when coping with the implementation of these standards within their local environment. Data: We selected a total of 33 items from these scales that match most with the objective of our survey. We also added the two questions posed by Berry to determine its acculturation strategies. We used 874 answers from different countries to our questionnaire. Tools: By taking Berry's typology, we conducted a cluster analysis to dynamic clouds using SPSS, which allows us to identify the different acculturation strategies used by respondents. Findings: Using Berry's acculturation model borrowed from social psychology and adopting an exploratory perspective based on the interpretive approach, we developed a measurement scale through which we identified five new acculturation attributes: interpersonal communication, work performance, open-mindedness, ethnocentrism and knowledge of the host culture. We also found that the integration strategy is the most widespread strategy in a new cultural context. This finding corresponds to the convergence strategy that is most solicited by countries applying IFRS. Contribution: Our research is an adaptation and extension of the acculturation model across some countries that could function as a "map" of potential interventions to strengthen local application of IFRS.
Keywords: M40; 650; culture; acculturation attitudes; accounting standardization strategies; IFRS